The evaluation of patient safety incident reporting at the Yogyakarta Gondomanan Health Center using the Health Matrix Network - Nur Syarainingsih Syam; Eko Yanuardi; Siti Kurnia Widi Hastuti (Riset Informasi Kesehatan, 2023)
Background: Based on patient safety incident data, the Ministry of Health, it is known that incident cases that occurred in the Special Region of Yogyakarta Province were 13.8%. Based on Patient safety’s policy in Indonesia namely PMK No. 11 of 2017 concerning patient safety states that every health service facility is required to have an information system that is used to improve patient safety, including the health center. The purpose of this study was to evaluate the use of the patient safety incident information system at the Gondomanan Health Center by using the Health Matrix Networks. Methode: This study uses a qualitative descriptive method with a case study design. Data collection used interview guidelines with 5 informants, namely the head of the health center, the patient safety team (1 doctor, 1 midwife, 1 nurse) and the dental polyclinic service coordinator (1 poly nurse). The sampling technique used purposive sampling. Result: There are 6 Health Matrix Network (HMN) tools that are used to measure the evaluation of patient safety information systems, namely information system resources, information system indicators, data sources, data management, CIS information products, and dissemination and use of SIK information. In terms of resource attributes or variables (policies, human resources, facilities and infrastructure and finance), health indicators, data sources, information products and the use of IKP reporting information are in accordance with the patient safety incident reporting guideline policy, and PMK No. 11 of 2017. Meanwhile, the attributes of data management and information products in the patient safety reporting information system have not been implemented optimally. Conclusion: The information system for reporting patient safety incidents at the Gondomanan Health Center requires improvement in procuring special SOPs for internal reporting of patient safety incidents which are part of the data management attributes.